Three new species of Bomarea (Alstroemeriaceae) from the Andean region of Colombia (2005)
ABSTRACT: Three new species of Bomarea (Alstroemeriaceae), B. caucana, B. euryantha, and B. straminea. found during a revision of the genus for the Flora of Colombia, are described and illustrated and their relationships discussed.